Physiological Responses of Crotalaria spp. to the Presence of High Aluminum Availability in the Soil - dos Santos, Beatriz Silvério [UNESP]; Ferreira, Tassia Caroline [UNESP]; Olívio, Maiara Luzia Grigoli [UNESP]; de Souza, Lucas Anjos; de Camargos, Liliane Santos [UNESP] (MDPI, 2024)
Brazilian soils are predominantly rich in aluminum, which becomes mobile at pH < 5, affecting sensitive plants; however, some species have developed aluminum tolerance mechanisms. The purpose of this study was to compare the physiological responses of Crotalaria genus species, family Fabaceae, which have the ability to associate with nitrogen-fixing bacteria under the influence of Al3+ in the soil. The soil used was Oxisol; the experimental design was in randomized blocks in a factorial scheme (2 × 3): soil factor (available toxic aluminum content; correction of dolomitic limestone—MgCO3) and species factor (C. juncea; C. spectabilis; C. ochroleuca); cultivated within 43, 53, and 53 days, respectively, with five replications; 30 experimental samples. Mass and length, pigments, gas exchange, and changes in nitrogen metabolism were evaluated. C. juncea showed a higher concentration of amino acids in the leaves, internal carbon, and stomatal conductance in soil with Al3+, as well as higher production of ureides, allantoinic acid, allantoic acid, proteins, and amino acids in the nodules, with 78% of the Al3+ accumulation occurring in the roots. C. ochroleuca demonstrated greater shoot length and nodule number production in limed soil; in soil with Al3+, it showed a 91% increase in chlorophyll a content and 93% in carotenoids. C. spectabilis showed a 93% increase in ureide production in the leaves in soil with Al3+.
Keywords: biological fixation; Fabaceae; leguminosae; liming; nitrogen metabolism; potentially toxic element